Christian Family as Domestic Church in the Writings of St. John Chrysostom - Widok, Norbert; Grzybowski, Wacław (Studia Ceranea, 2013)
John Chrysostom, the most famous preacher of the Eastern Empire, exerted an important influence on the formation of family. In his homilies he instructed fathers and mothers about their pedagogical tasks, and spoke of religious upbringing of children, which was directly linked with the well being of Christian family. Commenting on St. Paul’s letters, he started propagating the idea of “domestic church,” since it performs the role of a place where sanctification of human being occurs. The father of the family performs in such situation the tasks of a bishop, i.e. a guide in religious life. He should take care of the reading of the Holy Scriptures, the practice of prayer and catechetical teaching, which lead to proper level of faith and Christian morality. According to Chrysostom, systematic introduction of these religious practices in the family contributes to increase in piety among members, as well as social responsibility. The well formed family offers proper foundation for the transmission of religious tradition and significant link in social relations.